Análise das habilidades sociais de adolescentes com e sem indicadores de dotação e influências sociodemográficas - Martins, Cláudia Solange Rossi (Universidade Federal de São Carlos, 2013)
The issue of social performance of gifted individuals is a topic full of controversy in the specific literature for the fact that it brings antagonistic opinions on their predispositions to submit or not a social adjustment, especially in the stage of adolescence. The first position argues that, in general, they are more socially adjusted in relation to their peers without indication of giftedness because they understand that their high cognitive ability gives them a higher level of sensitivity to cope with interpersonal problems. The second position considers that the gifted have greater difficulty in social adjustment, because their extreme sensitivity leads to the adoption of the conducts poorly understood by peers, generating very poor social adjustments. Although the causes of such difficulties are less known, studies suggest that, in many cases, difficulties in social interactions result from a deficit social repertoire. Before, the general objective of this study was to analyze the social skills of adolescents with and without giftedness indicators and sociodemographic influences. As specific goals, the study sought to: (1) characterize the sample starting sociodemographic data (gender, age, education, advancement, economic class, degree of responsible financial of the family); (2) to compare difficulties and frequencies of these social repertoires; (3) to compare and to relate the frequencies and difficulties of their social repertoires to the sociodemographic variables and participation in other environments.The target population was consisted of 132 adolescents aged 12 to 18 of whom 72 were identified as gifted and 60 without indication of giftedness, all belonging to regular public schools in Lavras - Minas Gerais, Southern Brazil. Three selfreport instruments were used to collect data: the Economic Classification Criteria Brazil (CCEB); an Academic Data Form (FDA), and the Inventory of Social Skills of adolescents (IHSA-Del Prette). Data were analyzed by descriptive analysis, inferential and multivariate, using the statistical software SPSS (Statistical Product and Service Solutions). The results obtained from the characterization sample a from sociodemographic data showed starting from an equivalent distribution between the two groups. Similarly, the results obtained from the comparison between the frequencies and difficulties of the social repertories in this sample, revealed no significant difference between the groups regarding the frequency of social skills. However, they revealed difficulty on the subescale Affective Approach to the gifted adolescents. The comparison between the frequencies of difficulties and social repertoires sample to the sociodemographic variables and participation in other environments, not reveal significant differences between groups in variables: age, economic class, and instruction of the person who is financially responsible for the family. However it revealed significant differences between groups in variables: gender, education, advancement and participation in other environments. Finally the results of the relation between the frequencies of the repertoires and social difficulties of the sample, in relation to sociodemographic variables and participation in other environments showed significance only in some cases, for both groups. These results are similar to most of those obtained in other studies on the social repertoire of gifted adolescents, and show their relevance to indicate data on their actual social needs.
Keywords: Educação especial; Habilidades sociais; Adolescentes; Dotação; Social Skills; Teenagers; Giftedness; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL